Optimal utilization of fodder banks for the reproductive efficiency of Bunaji cattle: Effect of dry season forage legume supplementation on weight and reproductive performance - Mani, R.I.; Kaufmann, Ralph R. von; Egan, A.R.; Oyedipe, E.O.; Dixon, Rob M.; Holmes, J. (Nigeria Ministry of Agriculture and Water Resources, 1993)
This study arose from the need to develop strategies that optimize the use of available feed resources from natural range fallow and crop residues in combination with the fodder bank innovation. The paper discusses the interactive effects of feeding both forage legume and urea molasses supplements. Since rumen flora can use non protein nitrogen (NPN) to satisfy its nitrogen (N) requirement. It was hypothesized that feeding urea molasses would raise the efficiency of utilization of natural pasture and would have a positive interactive effect with forage legume supplementation. Five treatment groups were therefore formed so that animals were either solely grazed on natural range or 2) supplemented by having access to conserved natural pasture, or 3) molasses urea blocks or 4) leguminous fodder banks and molasses urea blocks or 5) leguminous fodder banks.